2018
DOI: 10.1093/femsle/fny065
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of AmpG in mediating a dynamic relationship between serine beta-lactamase induction and biofilm-forming ability of Escherichia coli

Abstract: AmpG permease is implicated both in beta-lactamase induction and peptidoglycan recycling in enterobacterial isolates. Here, physiological studies using molecular genetics show that deletion of AmpG permease dramatically increases beta-lactam susceptibility even in the presence of AmpC, TEM-1 and OXA beta-lactamases. Also, there is an appreciable decrease in the biofilm-forming ability of strains lacking this protein. Expression of this permease in excess probably compromises the integrity of the bacterial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Similarly, the Δ ampE strain showed a 2-fold increased sensitivity to amoxicillin, cefalothin and cefoxitin. In line with this observation, the effect of elevation of the beta-lactam susceptibility was also reported in the case of the Δ ampG mutant [ 20 ].…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Similarly, the Δ ampE strain showed a 2-fold increased sensitivity to amoxicillin, cefalothin and cefoxitin. In line with this observation, the effect of elevation of the beta-lactam susceptibility was also reported in the case of the Δ ampG mutant [ 20 ].…”
Section: Resultssupporting
confidence: 64%
“…Upon activity of beta-lactams, possibly at the sub-inhibitory level, the PG fragments are transported back to cytoplasm with the assistance of AmpG permease. Recently, it has also been reported that suppression of AmpG permease can efficiently inhibit both BLA induction and biofilm formation [ 20 ]. The accumulated cytoplasmic PG fragments help in the triggering of the AmpC induction via a transcriptional regulator, AmpR (a lysR type of regulator) [ 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…388,389 Nonetheless, it is evident that the full breadth of the roles of AmpG in muropeptide recycling, β -lactam susceptibility, and biofilm formation has yet to be determined. 390 A complementary approach to AmpG inhibition, given that this permease is driven by the proton-motive force (PMF), 277 is inhibition of this force. Indeed, this may be the mechanism of the structures identified through screening.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously shown that AmpG inactivation prevents the entrance of NAG-anhNAM-peptides and consequently the cytosolic accumulation of AmpC-activator signals, thereby disabling ampC overexpression (47, 7680). These facts are confirmed by our results, in which ampG deletion drastically decreased the intracellular accumulation of anhNAM-P3 and anhNAM-P5 in PAO1 but also in the high-level hyperproducer mutants in comparison with the respective parent strain, which leads to a block of ampC expression.…”
Section: Discussionmentioning
confidence: 99%